2019
DOI: 10.1002/jrs.5706
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure‐induced phase transition in 1,3‐diphenylurea: The approaching of N–H⋯O hydrogen‐bonded chains

Abstract: The crystal structure and hydrogen‐bonded chains of 1,3‐diphenylurea were found to have abrupt changes when the pressure increased to 1.8 GPa. Based on Raman spectra, the intermolecular interactions, the vibrations of chemical groups, and the molecular conformation were clearly distinguished from the initial state. The anisotropic compression of the original crystal structure and the occurrence of structural phase transition were confirmed by the results of in situ high‐pressure synchrotron X‐ray diffraction e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…[19],[20] We studied further in the exploded view of the fingerprint (Figure 6). Obviously, the ratios of H…Br interactions occupy the 43.5% of the total hirshfeld surface in 1‐LTP , but 1‐RTP is 36.8%, this phenomenon indicates an increase in the hydrogen bond interaction among the inorganic chain and organic cation [21] . For example, the spike marked with a red circle extends from (d i , d e )=(0.9, 1.7) to (0.8, 1.5) during the cooling process, this spike is inferred from Table S2 and S3 to be related to O−H…Br hydrogen bond [22] .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[19],[20] We studied further in the exploded view of the fingerprint (Figure 6). Obviously, the ratios of H…Br interactions occupy the 43.5% of the total hirshfeld surface in 1‐LTP , but 1‐RTP is 36.8%, this phenomenon indicates an increase in the hydrogen bond interaction among the inorganic chain and organic cation [21] . For example, the spike marked with a red circle extends from (d i , d e )=(0.9, 1.7) to (0.8, 1.5) during the cooling process, this spike is inferred from Table S2 and S3 to be related to O−H…Br hydrogen bond [22] .…”
Section: Resultsmentioning
confidence: 94%
“…Obviously, the ratios of H…Br interactions occupy the 43.5% of the total hirshfeld surface in 1-LTP, but 1-RTP is 36.8%, this phenomenon indicates an increase in the hydrogen bond interaction among the inorganic chain and organic cation. [21] For example, the spike marked with a red circle extends from (d i , d e ) = (0.9, 1.7) to (0.8, 1.5) during the cooling process, this spike is inferred from Table S2 and S3 to be related to OÀ H…Br hydrogen bond. [22] Combined with the previous structural analysis, it can be inferred that the change of hydrogen bond is also an important factor in the occurrence of phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bond, H⋯Br, depicts a sharp peak in the fingerprint plot. 31 The 2D fingerprint plot revealed that the highest contribution was from the H⋯Br interaction (51.0%) at T tr -1. However, with an increase in temperature, the contribution of the H⋯Br interaction decayed to 43.9% at T tr -2, and finally, to 5.9% at T tr -3.…”
Section: Resultsmentioning
confidence: 97%
“…Dai et al [ 178 ] described the high‐pressure‐induced phase transition in 1,3‐diphenylurea by considering the spatial approach of N‐H…O hydrogen‐bonded chains. Their study demonstrates that excessively reducing the space between hydrogen‐bonded chains will rearrange the self‐assembly of supramolecular materials.…”
Section: High Pressure Temperature Studies Phase Transitions and Gmentioning
confidence: 99%